How is the trade-off between adverse selection and discrimination risk affected by genetic testing? : theory and experiment (2017)
We compare two genetic testing regulations, Disclosure Duty (DD) and Consent Law (CL), in an environment where individuals choose to take a genetic test or not. DD forces agents to reveal the test results to their insurers, resulting in a discrimination risk. CL allows agents to withhold that information, generating adverse selection. We complement our model with an experiment. We obtain that a larger fraction of agents test under CL than under DD, and that the proportion of individuals preferring CL to DD is non-monotone in the test cost when adverse selection is set endogenously at its steady state level.